PERENCANAAN USAHA PAKAN TERNAK SAPI BUMDES WARU TIMUR, KECAMATAN WARU, KABUPATEN PAMEKASAN - SUCI FIRDAUS; MARDIYAH HAYATI; ISDIANA SUPRAPTI; FUAD HASAN; Fuad Hasan (GANEC SWARA, 2023)
The large number of cows in East Waru Village makes the need for cattle feed also higher. However, the availability of fodder is still relatively insufficient, especially during the dry seasons. This provides an opportunity for East Waru BUMDes to build a cattle feed business. This study aims to determine market conditions through Primary Market Research  and identify the East Waru BUMDs cattle feed business model. The research method used is descriptive qualitative research and Primary Market Research will be conducted on 94 farmers in East Waru Village and then develop a Business Model Canvas. The results of Primary Market Research show that 86% of farmers are interested in buying fermented cattle feed that will be sold by BUMDes Wartim Maslahah. Moreover, the need for feed also increases. The cattle feed business will start running if all the plans and costs are in place. The BUMDes plan is to synergize with the local government and work with farmer groups in marketing their products. All total costs have also been predicted so that you can calculate what needs to be prepared. It is hoped that the results of the BMC can help the process of establishing a livestock feed business belonging to BUMDes Wartim Maslahah so that it runs smoothly.